Shadow Lobbyists - Rocco D'Este; Mirko Draca; Christian Fons-Rosen (Institute of Labor Economics (IZA), 2023)
Special interest influence via lobbying is increasingly controversial and legislative efforts to deal with this issue have centred on the principle of transparency. In this paper we evaluate the effectiveness of the current regulatory framework provided by the US Lobbying Disclosure Act (LDA). Specifically, we study the role of ex-Congressional officials who join US lobbying firms in positions that could be related to lobbying activity but without officially registering as lobbyists themselves. We find that firm lobbying revenues increase significantly when these potential 'shadow lobbyists' join, with effects in the range of 10-20%. This shadow lobbyist revenue effect is comparable to the effect of a registered lobbyist at the median of the industry skill distribution. As such, it is challenging to reconcile the measured shadow lobbyist effect with the 20% working time threshold for registering as a lobbyist. Based on our estimates, the unaccounted for contributions of unregistered lobbyists can be valued at 149 million USD in revenue terms and this effect is concentrated within the industry's largest and most active firms.
Keywords: D72; 330; lobbying; revolving door; political money